Towards a dynamic knowledge-based approach to the innovation process: an empirical investigation on social capital inside an industrial cluster. (31st May 2007) - Pirolo, Luca; Presutti, Manuela
During recent years, the importance of the economic forces acting on firms' innovation performance has received much attention from economists and management scholars. In particular, the focus of the studies concerning innovation process has shifted from the control of static, firm-specific resources to the acquisition, assimilation and exploitation of firm-specific knowledge. This paper aims to identify a direct tie between a firm's social capital and its abilities and skills in the innovation process. We propose that the greater the social capital possessed by the firm, the greater its knowledge will be, and therefore, the faster its innovation process. Our results show a positive correlation between innovation performances and knowledge acquisition, supporting the hypothesis that knowledge acquisition mediates the relationship between social capital and innovation performances. These findings can offer some interesting reflections in the field of research innovation into social capital and innovation.